2017
DOI: 10.1093/mnras/stx2635
|View full text |Cite
|
Sign up to set email alerts
|

A scale-dependent bias on linear scales: the case for H i intensity mapping at z = 1

Abstract: Neutral hydrogen (HI) will soon be the dark matter tracer observed over the largest volumes of Universe thanks to the 21 cm intensity mapping technique. To unveil cosmological information it is indispensable to understand the HI distribution with respect to dark matter. Using a full one-loop derivation of the power spectrum of HI, we show that higher order corrections change the amplitude and shape of the power spectrum on typical cosmological (linear) scales. These effects go beyond the expected dark matter n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…In Section 5, we found that the halo H I mass function, M H I (M, z), from IllustrisTNG can be well reproduced by a fitting formula like - has been widely used (e.g., Bagla et al 2010;Obuljen et al 2017;Villaescusa-Navarro et al 2017;Pénin et al 2018). We have fit our results to that function, and while the reduced χ 2 is larger than that with our fiducial function, it is still a good fit to the underlying data.…”
Section: Appendix E Halo H I Mass Functionmentioning
confidence: 54%
See 1 more Smart Citation
“…In Section 5, we found that the halo H I mass function, M H I (M, z), from IllustrisTNG can be well reproduced by a fitting formula like - has been widely used (e.g., Bagla et al 2010;Obuljen et al 2017;Villaescusa-Navarro et al 2017;Pénin et al 2018). We have fit our results to that function, and while the reduced χ 2 is larger than that with our fiducial function, it is still a good fit to the underlying data.…”
Section: Appendix E Halo H I Mass Functionmentioning
confidence: 54%
“…A more conventional parameterization of the halo H I mass function falls more slowly for very low halo masses than the standard profile. In order to facilitate the comparison with works using the above parameterization (e.g., Bagla et al 2010;Obuljen et al 2018a;Villaescusa-Navarro et al 2017;Pénin et al 2018), we also provide the best-fit values for the more conventional fit in Appendix E.…”
Section: Halo H I Mass Functionmentioning
confidence: 99%
“…The bias can be measured on simulations simply computing the HI power spectrum (shot noise subtracted) and the matter power spectrum P m (k). On large scales, b HI (k) is expected to be roughly constant, while at small scales it has a more complex behavior (e.g Guha Sarkar et al 2012;Camera et al 2013;Pénin et al 2018). This is shown in figure 12, where the large scale measurements are noisy due to sample variance.…”
Section: Hi Biasmentioning
confidence: 99%
“…Therefore, considering more realistic models or measurements from numerical simulations is of great importance for robust cosmological analyses. To predict the Hi bias, halo model approach has been considered (Padmanabhan et al 2017;Pénin et al 2018), and several work have been done using pure N-body simulations (Sarkar et al 2016;Sarkar & Bharadwaj 2018). They do not fully solve the radiative transfer but populate the Hi according to the mass of the host dark matter halo.…”
Section: Introductionmentioning
confidence: 99%